The Effect of Financial Literacy and Lifestyle on Financial Behavior through Income in Employees of Penthouse 19th Medan - Nurianna Sihombing; Maya Macia Sari (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of financial literacy and lifestyle on financial behavior through income intervening variables in Penthouse 19 year old employees. The location of this research was carried out at the Penthouse 19th Medan Restaurant. This type of research is a descriptive research with a quantitative approach, with the SmartPLS analysis method assisted by SmartPLS Software 4.1.0.4. The sample of this study was 60 respondents who were employees of Penthouse 19th. The results of this study showed that Financial Literacy (X1) did not have a significant positive effect on Financial Behavior (Y), Financial Literacy (X1) did not have a significant positive effect on Income (Z), Lifestyle (X2) had a significant positive influence on Financial Behavior (Y), Lifestyle (X2) did not have a significant positive effect on Income (Z), Income (Z) did not have a significant positive effect on Financial Behavior (Y), Financial Literacy does not have a significant positive effect on Financial Behavior through Income, Lifestyle does not have a significant positive effect on Financial Behavior through Income.